Mechanisms underlying the tissue-specific and regulated activity of the Gnrhr promoter in mammals - Schang, Anne-Laure; Quérat, Bruno; Simon, Violaine; Garrel, Ghislaine; Bleux, Christian; Counis, Raymond; Cohen-Tannoudji, Joëlle; Laverrière, Jean-Noël (Frontiers in Endocrinology, 2012)
The GnRH receptor (GnRHR) plays a central role in the development and maintenance of reproductive function in mammals. Following stimulation by GnRH originating from the hypothalamus, GnRHR triggers multiple signalling events that ultimately stimulate the synthesis and the periodic release of the gonadotropins, luteinizing-stimulating hormone (LH) and follicle-stimulating hormones (FSH) which, in turn, regulate gonadal functions, including steroidogenesis and gametogenesis. The concentration of GnRHR at the cell surface is essential for the amplitude and the specificity of gonadotrope responsiveness. The number of GnRHR is submitted to strong regulatory control during pituitary development, estrous cycle, pregnancy, lactation, or after gonadectomy. These modulations take place, at least in part, at the transcriptional level. To analyse this facet of the reproductive function, the 5' regulatory sequences of the gene encoding the GnRHR have been isolated and characterized through in vitro and in vivo approaches. This review summarizes results obtained with the mouse, rat, human and ovine promoters either by transient transfection assays or by means of transgenic mice.